Multivariate data analysis of natural mineral waters - Šnuderl, Katja (Acta chimica slovenica, 2007)
Fifty samples of natural mineral waters from springs in Slovenia, Hungary, Germany, Czech Republic and further countries of former Yugoslavia have been analysed. The mass concentration of cations (Na+, K+, Ca2+, Mg2+, Fe2+, Mn2+, NH4+) and anions (F-, Cl-, I-, NO3-, SO4 2-, HCO3-), the spring temperature, pH, conductivity and carbon dioxide mass concentration have been measured using standard analytical methods. Appropriate statistical methods and different chemometric tools were used to evaluate the obtained data, namely, (i) descriptive statistics, (ii) principal component analysis (PCA), (iii) cluster analysis, and (iv) linear discriminant analysis (LDA). It was confirmed that Slovenian natural mineral water samples differ most from the German ones but are relatively similar to the Czech and Hungarian ones. Water samples from Hungary are similar to waters from the eastern part of Slovenia.
Keywords: kemijska analiza; mineralne vode